Vocabulary learning beliefs, strategies and size: a study of undergraduate learners of engineering and technical courses in public institution in Pahang / Rashidah Abdul Kadir - Abdul Kadir, Rashidah (2014)
Most of public higher institutions in the field of Engineering and Technology have chosen English as medium of instruction in their teaching and learning. As the language still retains a significant role in the profession, more steps need to be taken as to improve learners’ chances for employment. Unquestionably, language proficiency demand a wide array of English vocabulary as to perform better in all its four skills, i.e. reading, writing, speaking and listening. Thus, the aim of the present study is to capture the beliefs and strategies as well as establish a relationship between beliefs and strategies and strategies with vocabulary size of learners. Furthermore, this study tries to find out whether learners' reported vocabulary learning beliefs and strategies comparable with what their lecturers perceived. As to achieve these objectives, a questionnaire, a vocabulary test and a semi-structured interview were used for data collection. 165 learners completed the questionnaire and the vocabulary test. Follow up interview were conducted with two lecturers from the participating classes involved. The descriptive analysis and two types of correlation coefficient analysis were used to answers the research questions. Subsequently, transcriptions of the interview were coded and themed accordingly. Analysis of the data revealed that learners generally have positive beliefs about vocabulary learning. They believed that acquisition and motivation is important to their success in learning the skill. Moreover, the analysis also suggests that metacognitive strategies is commonly used by learners while cognitive strategies are the least used strategies by learning vocabulary although it is reported that most learners used dictionary to find meaning of new words. Furthermore, synthesis on these two results revealed the significant correlation between learners’ beliefs and strategies used. Whereas weak or negative correlation was found between learners’ frequency used strategies with their vocabulary size. On the other hand, several similarities found between learners reported beliefs and strategies used in learning vocabulary with what the lecturers perceived. Nonetheless, few discrepancies especially in metacognitive regulation were found between what reported by learners with what their lecturers perceived. Generally, this study shows that most learners still rely on dictionary in learning vocabulary. Very few learners were familiar with more concrete strategies which would lend more success in vocabulary learning. Hence, it is hoped that the present study may induce more strategies for learners and is compatible with the approach used by their lecturers; which would improve the effectiveness of English Language teaching and learning.